2022
DOI: 10.3899/jrheum.211288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatigue on Health-Related Quality of Life and Work Productivity in Psoriatic Arthritis: Findings From a Real-World Survey

Abstract: Objective To evaluate fatigue frequency and severity among patients with psoriatic arthritis (PsA) and assess the impact of fatigue severity on patient-reported outcome measures (PROMs) assessing quality of life, function, and work productivity. Methods Data were derived from the Adelphi Disease Specific Programme, a cross-sectional survey conducted in 2018 in the United States and Europe. Patients had physician-confirmed PsA. Fatigue was collected as a binary variable and through its severity (0-10 scale, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
6
0
2
Order By: Relevance
“…We additionally observed that both dosing regimens of IXE were effective in reducing fatigue in patients across psoriasis severity groups, compared to treatment with PBO, over 24 weeks. Reducing fatigue among the patient population under study has the potential to improve patient well-being and daily function, which may encourage greater compliance with prescribed treatment regimens, fostering better long-term health outcomes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We additionally observed that both dosing regimens of IXE were effective in reducing fatigue in patients across psoriasis severity groups, compared to treatment with PBO, over 24 weeks. Reducing fatigue among the patient population under study has the potential to improve patient well-being and daily function, which may encourage greater compliance with prescribed treatment regimens, fostering better long-term health outcomes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of disease activity was not collected since a widely accepted index for measuring disease activity in PsA is lacking [39]. Further, experiences of pain are not exclusively correlated to disease activity but are also related to factors such as fatigue [40], and activity limitations [41], data on which were collected. Our sample included only a few men, which might not mirror the population.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was shown that fatigue severity was associated with poorer health status, physical functioning, work productivity, and health-related life quality. Patients reporting higher levels of fatigue were older, had higher disease activity and perceived pain levels, had a longer time since diagnosis and symptom duration, and had more frequent anxiety/depressive symptoms [100]. Reduction in disease activity is associated with lower fatigue levels, and decreased fatigue levels were observed in 81.5% of patients with very low disease activity (VLDA).…”
Section: Fatigue In Psoriatic Arthritismentioning
confidence: 99%